When principles and pedagogy clash: Moving beyond the limits of scholarly practices in an academic-community partnership with sex worker activists. Issue 10 (3rd October 2022) - Daryani, Poonam; Ensha, Leila; Frank, Mariah; Kofke, Lily; Maviglia, Francesca; Miller, Alice M.
ABSTRACT: While U.S. public health education increasingly promotes community-based participatory research (CBPR) as a mode of socially-responsive research, today's intertwined health and social injustice crises demand honest reckoning with the limitations of CBPR as a framework for change. We are a team of students, fellows, and faculty reflecting on the complexities encountered over three years of collaborative work with street-based sex worker activists, in a city characterised by stark wealth disparities reinforced by policies of the university within which we operate. We centre a peer-based needs assessment survey and report on barriers to resources and services for sex workers to highlight hard choices and often unacknowledged challenges to academic partnerships. Our process intends to unsettle the too-sanguine narratives of CBPR, draw from insights arising in the discipline of law, and illuminate practices needed to honour commitments, translate knowledge to power-shifting action, and constructively engage with those most affected in determining the policies that structure their lives. We ask: Can our privileged position within the academy be usefully analysed, confronted, instrumentalised, and even subverted as we shape new practices and interventions in the name of health justice? How might we imagine principles and practices towards a movement public health?